Hemodialysis systems (ANSI/AAMI, 1993)
This standard establishes requirements for material, components, monitors and alarms, accessories, and labeling for dialysate supply and water treatment equipment. The quality of water and hemodialysis concentrate used in the system is also defined. Additionally, a guideline for the device user, with particular emphasis on water purity assurance and monitoring, is appendende to this standard.